2013
DOI: 10.1371/journal.pone.0059062
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms within Human Follicular Fluid: Effects on IVF

Abstract: Our previous study reported microorganisms in human follicular fluid. The objective of this study was to test human follicular fluid for the presence of microorganisms and to correlate these findings with the in vitro fertilization (IVF) outcomes. In this study, 263 paired follicular fluids and vaginal swabs were collected from women undergoing IVF cycles, with various causes for infertility, and were cultured to detect microorganisms. The cause of infertility and the IVF outcomes for each woman were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 42 publications
5
75
0
Order By: Relevance
“…and oral mucosa (Streptococcus spp. ), which supports the hypothesis that the follicular fluid does not always get contaminated during oocyte retrieval and can be colonized before this procedure [56]. So far, there has been no research to assess the vaginal, cervical, endometrial, fallopian, follicular and peritoneal microbiomes in parallel.…”
Section: The Microbiome Of Ovarian Folliclessupporting
confidence: 66%
See 1 more Smart Citation
“…and oral mucosa (Streptococcus spp. ), which supports the hypothesis that the follicular fluid does not always get contaminated during oocyte retrieval and can be colonized before this procedure [56]. So far, there has been no research to assess the vaginal, cervical, endometrial, fallopian, follicular and peritoneal microbiomes in parallel.…”
Section: The Microbiome Of Ovarian Folliclessupporting
confidence: 66%
“…РАK kinases phosphorylate some cytoskeletal proteins and regulate their activity. Some authors indicate their role in the regulation of MAPK signal pathways in mammalian cells [56,57]. Kinases of the NDR family were shown to have a role in embryonic development, neurological processes and cancer mechanisms [58].…”
Section: Practical Application Of the Proposed Classification: Selectmentioning
confidence: 99%
“…**P ≤ 0.05; *P ≤ 0.08 compared with untreated controls; analysis by nonparametric Mann-Whitney U test. ovarian follicle and that patients suffering PID show ovarian pathologies (Bychkov 1990, Pelzer et al 2011, Pelzer et al 2013. The data presented here suggest that GLCs can initiate an innate immune response to pathogen-associated molecules, potentially altering the microenvironment of the follicle.…”
Section: Discussionmentioning
confidence: 75%
“…Retrospective analysis of patients undergoing fertility treatment suggest that increased endometrial LPS reduces IVF success (Kamiyama et al 2004). More recently, it has been demonstrated that bacteria can be isolated from the follicular fluid of women undergoing infertility treatment, with the extent of bacterial colonization of the follicle being correlated with the success of fertility treatment (Neuer et al 1997, Pelzer et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, various studies [modulo the usual issues of contamination (418)] have shown the presence of microbes in tissues including the placenta (400, 409, 419432), vagina (393, 433440), uterus (391, 441, 442), amniotic fluid (430, 443448), and follicular fluid (449, 450), and how these may vary significantly in PE [we do not discuss other pregnancy disorders such as small for gestational age (SGA) and intrauterine growth restriction (IUGR)]. We list some of these in Table 3.…”
Section: Direct Evidence For a Role Of Infectious Agents In Pementioning
confidence: 99%